Charge states and lattice sites of dilute implanted Sn in ZnO. (7th March 2017) - Mølholt, T E; Gunnlaugsson, H P; Johnston, K; Mantovan, R; Röder, J; Adoons, V; Mokhles Gerami, A; Masenda, H; Matveyev, Y A; Ncube, M; Unzueta, I; Bharuth-Ram, K; et al.
Abstract: The common charge states of Sn are 2+  and 4+. While charge neutrality considerations favour 2+  to be the natural charge state of Sn in ZnO, there are several reports suggesting the 4+  state instead. In order to investigate the charge states, lattice sites, and the effect of the ion implantation process of dilute Sn atoms in ZnO, we have performed 119 Sn emission Mössbauer spectroscopy on ZnO single crystal samples following ion implantation of radioactive 119 In ( T ½   =  2.4 min) at temperatures between 96 K and 762 K. Complementary perturbed angular correlation measurements on 111m Cd implanted ZnO were also conducted. Our results show that the 2+  state is the natural charge state for Sn in defect free ZnO and that the 4+  charge state is stabilized by acceptor defects created in the implantation process.